Making water affordable to all: A typology and evaluation of options for urban water pricing - Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2011)
An important criterion for the design of urban water prices is the affordability of water supply for poor customers. This paper presents a typology of water pricing options which policy-makers have at their disposal in order to address affordability. A review of theoretical insights and empirical experiences reveals, however, how the real-world performance of these options depends on the characteristics of their technological and socio-economic environment. Moreover, possible trade-offs between affordability and other criteria, including efficiency, financial sustainability and administrative simplicity, are pointed out. Thereby, the paper is meant to assist policy-makers in identifying water pricing options which are appropriate for their context.
Keywords: 330; administrative simplicity; affordability; efficiency; financial sustainability; typology; water pricing